بچوں پر ذہنی تشدد اور اس سے بچاؤ:اسلامی تعلیمات کی روشنی میں ایک مطالعہ (Al-Qamar, 2023)
Islam is a religion of mercy that teaches love to its followers. All human beings deserve this love, but children are the most deserving of it. They are generally loved but there are many children who are either exposed to physical abuse or psychological abuse in various ways. Emotional abuse refers to the habitual verbal harassment of a child by disparagement, criticism, threat, ridicule, and the inversion of love (by verbal and non-verbal means). According to an estimate, about 1 billion children experience sexual, physical, or mental violence in a year all over the world. Emotional unavailability, hostility, rejection, developmentally inappropriate interaction, and exposure to domestic violence are some examples of emotional abuse. Emotional abuse can have profound and long-lasting effects on a child's emotional, psychological, and social development, including low self-esteem, anxiety, depression, social isolation, and developmental delays. In this research, emotional abuse will be defined first, and then its types. Then its effects on the child will be shared. Finally, the Islamic teachings will be explained in detail on how to protect a child from mental abuse.
Keywords: Children; Emotional abuse; Physical Abuse; Islamic Teachings